(3GdEHGfI hGdEYdGe HZGjI GdEdgGe dEjVGM hJHjjf SdGeJg Udi Gddg Ydjg hSde Ydi ef CSde ef CeJg Ohf SGFQ GdCfGes - (3GdWQjfj, GdeGdcj, YHO GdLhGO Hf EHQGgje, (B1073 (3g`s ((3Rjf GdYGHOjf Hf RcQjG GdCfUGQj GdNRQLj GdTGaYjs)
(3ChdgG (B:s
(3HSe Gddg (B... (3deG PgH GdeYGUQhf hGdCJdGO GdPjf cGf Hge hYfge jHdZ GdSGFd cd eG CQGO hHbj ef geg GdOfjG hGdOQge JcGKQG ef GdYHGO (B...s
(3BNQgG (B:s
.... (3hHeG JbQQ Yde LhGH bhdg de jXgQ dj eYfi eJQJHjf EdN hgd GdLeY EdN hCgd GdChd hGdKGfj aXGgQ hCeG GdKGdK adCfg dG JNUjU MJi jWdH SQg (B.s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B2/50s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs